FUNGSI BAHASA DALAMTUTRAN RITUAL RANGGA NGINDI DEWA DALAM BUDAYA MASYARAKAT TANA RIGHU DI SUMBA BARAT - Ama Kamuri, Paulus; Sabon Ola, Simon (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
This article discusses the function of language in the Rangga Ngindi Dewa ritual speech in the Tana Righu community, West Sumba. Referring to the concept of language function according to Roman Jakobson, the results obtained regarding the language function implied in the Rangga Ngindi Dewa ritual speech are as follows: (1) phatic function is related to how to open and close communication with ancestral spirits; (2) emotional function related to expressing thoughts and feelings to the God and ancestral spirits; (3) the conative function is related to how to understand the responses of invisible participants; (4) and the poetic function is related to the element of aestetic in the use of language. These language functions constitute the entire linguistic structure of the Rangga Ngindi Dewa ritual speech which emphasizes transcendental communication.